ANALISIS KESALAHAN PEMAKAIAN BAHASA INDONESIA PADA PENULISAN PROPOSAL KEGIATAN PESERTA DIDIK KELAS XI IPS SMA NEGERI 7 KOTA KEDIRI TAHUN AJARAN 2021/2022 - Ganes Tegar Derana; Alifarose Syahda Zahra (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2021)
Language error analysis in particular has many advantages in language teaching. The existence of an analysis of language errors can find out the mistakes made in Writing Student Activity Proposals. This study generally aims to describe the analysis of vocabulary and spelling errors of class XI IPS SMAN 7 Kediri City students on the use of Indonesian when writing activity proposals. Specifically, the purpose of this study was to describe (1) the form of diction errors, (2) the form of spelling errors, and (3) the teacher's efforts to correct errors. Based on the results of the study, it can be concluded that (1) there is a form of diction error or word choice in Student Activity Proposal Writing for class XI IPS SMAN 7 Kediri City as many as 15 include, incorrect word choice (PKTT) 6 errors, inappropriate word (KTS) 5 errors, and ineffective words (KTE) 4 errors, (2) the form of spelling errors in Student Activity Proposal Writing for class XI SMAN 7 Kediri City as many as 63 errors including, capital letters (HK) 39 errors, italics (HM) 8 errors, punctuation marks (TB) 12 errors, and word writing (PK) 4 errors, (3) the teacher's efforts to correct errors in the use of Indonesian, first, increasing students' mastery of language rules, and second, to better understand the rules of language words and spelling, third , provide motivation for students to read, fourth, the models and learning methods used by the teacher will be more diverse and interesting. Keywords: language errors, efforts to overcome errors, activity proposal